Multimodal Management of Calvarial Osteosarcoma with en Bloc Craniectomy and Adjuvant Imatinib Therapy in a Dog - Yijae Kim; Wookhun Chung; Jaewoong Han; Byung-Joon Seung; Jungwhan Chon; Kihoon Kim (Veterinary Sciences, 2026)
An osteosarcoma (OSA) is a malignant mesenchymal tumor characterized by osteoid production by neoplastic osteoblasts. Particularly, calvarial OSA is an uncommon form of canine OSA. A 10-year-old male Pomeranian dog presented with a palpable calvarial mass. Computed tomography (CT) demonstrated a well-defined osseous mass arising from the left parietal bone without intracranial invasion or regional metastasis. An en bloc craniectomy including the affected calvarial bone was performed, and histopathological examination confirmed the diagnosis of OSA. Based on previous reports suggesting that PDGFR-mediated signaling may represent a potential therapeutic target in canine OSA, oral imatinib was planned to be administered for 1 year as postoperative adjuvant therapy. Seven months after surgery, follow-up CT showed no evidence of local recurrence or systemic metastatic disease. Ten months after surgery, the dog was re-evaluated for continued anticancer therapy, with no evidence of local recurrence on physical examination. This case suggests that satisfactory local tumor control can be achieved following surgical excision despite anatomically limited surgical margins. In addition, it provides clinical information regarding postoperative imatinib administration and CT follow-up for canine calvarial OSA. To the best of the authors’ knowledge, this is the first report describing adjuvant imatinib therapy following surgical treatment of canine calvarial OSA. However, further studies are warranted to determine the long-term efficacy of this treatment approach.